Measurement of Physical Workload Using the NIOSH (National Institute of Occupational Safety and Health) Method for Rice Transport Activities at Kranggot Market - Cilegon - Fitriani, Dwi; Amanda, Novita; Dewantari, Nustin Merdiana; Mariawati, Ade Sri; Herlina, Lely; Umyati, Ani (Universitas Sultan Ageng Tirtayasa, 2024)
Kranggot Market is one of the markets in the city of Cilegon. This traditional market sells various essential goods and basic necessities, one of which is rice. The rice sold at Kranggot Market is supplied from various regions, transported by supplier trucks to rice shops in the market. The rice offloaded from the trucks is typically carried directly by the workers of these shops. The loads carried by the workers vary, ranging from 5 kg to 50 kg, which can pose physical hazards to their bodies, such as bending issues, fractures, spine injuries, and other risks.To address these issues, a physical workload measurement is conducted on rice-carrying workers using the NIOSH method. The study aims to calculate the Recommended Weight Limit (RWL) and Lifting Index (LI), provide recommendations, and assess whether the lifting activities performed by the workers pose risks or are within safe limits. According to the calculation results, the RWL and LI values before the improvements were 10.21 and 4.90, respectively, at the origin position, and 12.67 and 3.95 at the destination position. After the suggested improvements were implemented, the RWL and LI values reached 46.32 and 1.08, respectively. It can be concluded that the recommended improvements using material handling can reduce the risk of injury to workers.